Differential Mechanisms of Septic Human Pulmonary Microvascular Endothelial Cell Barrier Dysfunction Depending on the Presence of Neutrophils - Wang, Lefeng; Mehta, Sanjay; Ahmed, Yousuf; Wallace, Shelby; Pape, M. Cynthia; Gill, Sean E. (Frontiers in Immunology, 2018)
Sepsis is characterized by injury of pulmonary microvascular endothelial cells (PMVEC) leading to barrier dysfunction and lung injury. Multiple mechanisms promote septic PMVEC barrier dysfunction, including interaction with circulating leukocytes and apoptotic death of PMVEC. Our previous work has shown a strong correlation between septic neutrophil-dependent PMVEC apoptosis and pulmonary microvascular albumin leak in septic mice in vivo; however, this remains uncertain in human PMVEC. Thus, we hypothesize that human PMVEC apoptosis is required for loss of PMVEC barrier function under septic conditions in vitro. To assess this hypothesis, human PMVECs cultured alone or in co-culture with neutrophils were stimulated with PBS or cytomix (equimolar interferon γ, tumour necrosis factor α, and interleukin 1β) in the absence or presence of Q-VD, a synthetic pan-caspase inhibitor. PMVEC barrier function was assessed by measuring transendothelial electrical resistance (TEER), as well as fluoroisothiocyanate-labeled dextran and Evans blue-labeled albumin flux across PMVEC monolayers. PMVEC apoptosis was identified by three molecular markers: (1) loss of cell membrane polarity (Annexin V), (2) caspase activation (FLICA), and (3) DNA fragmentation (terminal deoxynucleotidyl transferase dUTP nick end labeling [TUNEL]). Septic stimulation of human PMVECs cultured alone resulted in a loss of barrier function (decreased TEER and increased macromolecular flux) associated with increased apoptosis (increased Annexin V, FLICA and TUNEL staining). In addition, treatment of septic PMVEC cultured alone with Q-VD decreased PMVEC apoptosis and prevented septic PMVEC barrier dysfunction. In septic neutrophil-PMVEC co-cultures, there was greater trans-PMVEC macromolecular flux (both dextran and albumin) vs. PMVEC cultured alone. Neutrophil presence also augmented septic PMVEC caspase activation (FLICA staining) vs. PMVEC cultured alone, but did not affect septic PMVEC apoptosis. Importantly, caspase inhibition (Q-VD treatment) completely attenuated septic neutrophil-dependent PMVEC barrier dysfunction. Our data demonstrate that human PMVEC barrier dysfunction under septic conditions in vitro (cytomix stimulation) is clearly caspase-dependent, but the mechanism differs depending on the presence of neutrophils. In isolated PMVEC, apoptosis contributes to septic barrier dysfunction, whereas neutrophil presence enhances caspase-dependent septic PMVEC barrier dysfunction independently of PMVEC apoptosis.